Preparation method of mesoporous silicon-carbon composite material, mesoporous silicon-carbon composite material and application thereof
Patent Information
- Application Number
- CN202410563971.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-08
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2044-05-08
AI Technical Summary
[0002]当前的新型硅碳复合材料基本都是由多孔碳及其沉积在多孔碳孔隙中的纳米硅组成,然而由于多孔碳自身的电子导电性差及其孔容,造成其材料的电子导电性差,影响其应用电池的快充性能,此外,多孔碳结构材料的特性造成其副反应较多,会影响其应用电池的首次效率及其高温性能
[0021]This application first proposes using silica molecular sieves as templates, doping them into resin-based hard carbon. Simultaneously, by doping with an activator, during high-temperature carbonization, the activator volatilizes and forms pores. The gas generated during the heating and carbonization of organic carbonates leaves behind nanopores/micropores, significantly increasing the material's pore volume. Furthermore, the silica molecular sieve has a three-dimensional structure and large pore size, providing expansion space. This allows the mesoporous silica-carbon composite material formed by the interaction of porous carbon with the resin carbonization to provide favorable expansion space for subsequent silicon expansion, reducing silicon expansion. More importantly, the applicant has surprisingly discovered that using the mesoporous silica-carbon composite material provided in this application, nano-silicon can be deposited in its porous structure via silane pyrolysis. In addition to heteroatom gases, nano-silicon materials offer excellent capacity performance, and the heteroatoms formed after the heteroatom gases are cracked are used for doping to improve the electronic conductivity of the resulting silicon-carbon composite material, thereby improving its rate performance. This application further mixes silicon-carbon composite materials, silane coupling agents, asphalt, and conductive agent solutions. The organic functional groups of the silane coupling agent enable the amorphous carbon formed after the silicon-carbon composite material, conductive agent, and asphalt are carbonized to form a strong network structure, thereby improving the electronic conductivity of the material and reducing expansion. At the same time, the conductive agent and soft carbon are coated on the surface of the material, further improving the electronic conductivity of the composite material and reducing its surface defects, thereby improving the initial efficiency and high-temperature storage performance of the battery.
Smart Images

Figure CN118495535B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery material preparation, specifically relating to a method for preparing mesoporous silicon-carbon composite materials. This invention also relates to the mesoporous silicon-carbon composite materials prepared by this method and their applications. Background Technology
[0002] Current novel silicon-carbon composite materials are mostly composed of porous carbon and nano-silicon deposited in the pores of porous carbon. However, due to the poor electronic conductivity and pore volume of porous carbon itself, the electronic conductivity of the material is poor, which affects the fast charging performance of the battery. In addition, the characteristics of porous carbon structure materials cause more side reactions, which will affect the initial efficiency and high-temperature performance of the battery.
[0003] Therefore, based on the applicant's focused research experience in this field, we hope to find new technical solutions to address the above-mentioned technical problems. Summary of the Invention
[0004] In view of this, the purpose of the present invention is to provide a method for preparing mesoporous silicon-carbon composite material, the mesoporous silicon-carbon composite material and its application. The secondary particle silicon-carbon composite material prepared by using the mesoporous silicon-carbon composite material effectively reduces expansion and significantly improves the electronic conductivity of the material.
[0005] The technical solution adopted in this invention is as follows:
[0006] A method for preparing a mesoporous silicon-carbon composite material includes the following steps:
[0007] S11) The silica molecular sieve, activator and organic carbonate are mixed evenly and added to the resin solution and dispersed evenly to obtain a mixture;
[0008] S12) After spray drying the mixture obtained in step S11), pre-carbonize it at a temperature of 500-700°C for at least 5 hours, preferably 6-24 hours, and then pickle it to obtain the pre-carbonized intermediate material.
[0009] S13) The pre-carbonized intermediate material obtained in step S12) is transferred to a carbonization device, and carbon dioxide active gas with a flow rate range of 500-2000 SCCM is introduced into the carbonization device. The carbonization is carried out for 1-6 hours at a temperature of 800-1200℃ to obtain the mesoporous silicon-carbon composite material.
[0010] Preferably, in step S11), the mass ratio of the silica molecular sieve, activator, organic carbonate and resin is in the range of 100:1-10:10-30:100-500.
[0011] Preferably, in step S11), the activator is any one or a mixture of several of ZnCl2, ZnNO3 and ZnCO3; and / or the organic carbonate is any one or a mixture of several of sodium citrate, magnesium citrate, zinc citrate, calcium citrate, diammonium hydrogen citrate, ammonium hydrogen citrate and ammonium citrate.
[0012] Preferably, in step S11), the resin concentration in the resin solution ranges from 5 to 25 wt%, wherein the resin is any one or a mixture of several of urea-formaldehyde resin, polyimide resin, benzoxazine resin and polyarylacetylene resin; and / or the solvent in the resin solution is N-methylpyrrolidone.
[0013] Preferably, a mesoporous silicon-carbon composite material is prepared using the method described above for preparing mesoporous silicon-carbon composite materials.
[0014] Preferably, the mesoporous silicon-carbon composite material described above is used as a raw material for preparing secondary particulate silicon-carbon composite materials, wherein the secondary particulate silicon-carbon composite material includes the following preparation steps:
[0015] S21) The mesoporous silicon-carbon composite material is transferred to a fluidized bed, a silane mixed gas is introduced, and the material is pyrolyzed at a temperature of 400-500℃ to obtain a silicon-carbon precursor material. Then the temperature is lowered to 200-300℃, and an oxygen-containing gas with a flow rate of 100-500 SCCM is introduced for 30-300 minutes to obtain the silicon-carbon composite material.
[0016] S22) According to the mass ratio of silicon-carbon composite material: silane coupling agent: asphalt: conductive agent solution in the range of 100:0.5-2:1-5:100-500, the silicon-carbon composite material, silane coupling agent, asphalt and conductive agent solution obtained in step S21) are added to the carbonization equipment and dispersed evenly. Then, the temperature is raised to 250-400°C at 1-5°C / min and carbonized for at least 1 hour, preferably 1-6 hours. Then, the temperature is raised to 900-1200°C and held for at least 1 hour, preferably 1-6 hours. Then, the temperature is lowered in an inert atmosphere to obtain the secondary particle silicon-carbon composite material.
[0017] Preferably, in step S21), the silane mixed gas is composed of silane gas and heteroatom gas with a volume ratio ranging from 10:0.5-2 and a flow rate ranging from 100-500 SCCM; wherein the silane gas is any one or a mixture of several of silane, silane, and chlorosilane; the heteroatom gas is any one or a mixture of several of boron hydride, hydrogen sulfide, ammonia, and hydrogen boride; and / or the oxygen-containing gas is any one or a mixture of several of oxygen, carbon monoxide, carbon dioxide, nitric oxide, nitrogen dioxide, sulfur dioxide, and formaldehyde.
[0018] Preferably, in step S22), the silane coupling agent is any one or a mixture of several of γ-mercaptopropyltriethoxysilane (KH-580), γ-aminopropyltriethoxysilane (KH-550), γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560), bis-(γ-triethoxysilylpropyl)tetrasulfide (Si 69), and bis-(triethoxysilylpropyl)disulfide (Si75); and / or the asphalt is any one or a mixture of several of coal tar pitch, petroleum asphalt, and emulsified asphalt, with a softening point range preferably of 100-140°C, a volatile content preferably ≤60%, and a coking value preferably ≥40%.
[0019] Preferably, in step S22), the concentration of the conductive agent in the conductive agent solution is in the range of 0.5-5 wt%, the conductive agent is any one or a mixture of several of carbon nanotubes, graphene, carbon black and fumed carbon fibers, and / or the solvent in the conductive agent solution is N-methylpyrrolidone.
[0020] Preferably, the secondary particulate silicon-carbon composite material is used as the active material raw material for preparing battery electrodes, and more preferably as the active material raw material for lithium-ion battery negative electrode sheets.
[0021] This application first proposes using silica molecular sieves as templates, doping them into resin-based hard carbon. Simultaneously, by doping with an activator, during high-temperature carbonization, the activator volatilizes and forms pores. The gas generated during the heating and carbonization of organic carbonates leaves behind nanopores / micropores, significantly increasing the material's pore volume. Furthermore, the silica molecular sieve has a three-dimensional structure and large pore size, providing expansion space. This allows the mesoporous silica-carbon composite material formed by the interaction of porous carbon with the resin carbonization to provide favorable expansion space for subsequent silicon expansion, reducing silicon expansion. More importantly, the applicant has surprisingly discovered that using the mesoporous silica-carbon composite material provided in this application, nano-silicon can be deposited in its porous structure via silane pyrolysis. In addition to heteroatom gases, nano-silicon materials offer excellent capacity performance, and the heteroatoms formed after the heteroatom gases are cracked are used for doping to improve the electronic conductivity of the resulting silicon-carbon composite material, thereby improving its rate performance. This application further mixes silicon-carbon composite materials, silane coupling agents, asphalt, and conductive agent solutions. The organic functional groups of the silane coupling agent enable the amorphous carbon formed after the silicon-carbon composite material, conductive agent, and asphalt are carbonized to form a strong network structure, thereby improving the electronic conductivity of the material and reducing expansion. At the same time, the conductive agent and soft carbon are coated on the surface of the material, further improving the electronic conductivity of the composite material and reducing its surface defects, thereby improving the initial efficiency and high-temperature storage performance of the battery. Attached Figure Description
[0022] Figure 1 This is a flowchart illustrating the preparation steps of mesoporous silicon-carbon composite material according to a specific embodiment of the present invention;
[0023] Figure 2 This is a flowchart illustrating the preparation steps of the secondary particulate silicon-carbon composite material according to a specific embodiment of the present invention;
[0024] Figure 3 This is a SEM image of the secondary particle silicon-carbon composite material prepared in Example 1 of the specific embodiments of the present invention. Detailed Implementation
[0025] Please see Figure 1 As shown, this embodiment provides a method for preparing mesoporous silicon-carbon composite materials, including the following steps:
[0026] S11) The silica molecular sieve, activator, and organic carbonate are mixed evenly and added to the resin solution for uniform dispersion to obtain a mixture; preferably, in this step S11), the mass ratio of silica molecular sieve, activator, organic carbonate, and resin is in the range of 100:1-10:10-30:100-500; the activator is any one or a mixture of ZnCl2, ZnNO3, and ZnCO3; and / or the organic carbonate is any one or a mixture of sodium citrate, magnesium citrate, zinc citrate, calcium citrate, diammonium hydrogen citrate, ammonium hydrogen citrate, and ammonium citrate; the resin concentration in the resin solution is in the range of 5-25 wt%, wherein the resin is any one or a mixture of urea-formaldehyde resin, polyimide resin, benzoxazine resin, and polyarylacetylene resin; and / or the solvent in the resin solution is N-methylpyrrolidone;
[0027] S12) After spray drying the mixture obtained in step S11), pre-carbonize it at a temperature of 500-700°C for at least 5 hours, preferably 6-24 hours, and then pickle it to obtain the pre-carbonized intermediate material.
[0028] S13) The pre-carbonized intermediate material obtained in step S12) is transferred to a carbonization device, and carbon dioxide active gas with a flow rate range of 500-2000 SCCM is introduced into the carbonization device. The material is carbonized for 1-6 hours at a temperature of 800-1200℃ to obtain a mesoporous silicon-carbon composite material.
[0029] Preferably, this embodiment also proposes a mesoporous silicon-carbon composite material, which is prepared by the mesoporous silicon-carbon composite material preparation method described above.
[0030] Preferably, this embodiment also proposes an application of the mesoporous silicon-carbon composite material as described above, using it as a raw material for preparing secondary particulate silicon-carbon composite materials, wherein, please refer to Figure 2 As shown, the secondary particle silicon-carbon composite material includes the following preparation steps:
[0031] S21) The mesoporous silicon-carbon composite material is transferred to a fluidized bed, and a silane mixed gas is introduced. The material is then pyrolyzed at a temperature of 400-500℃ to obtain a silicon-carbon precursor material. The temperature is then lowered to 200-300℃, and an oxygen-containing gas with a flow rate of 100-500 SCCM is introduced for 30-300 minutes to obtain the silicon-carbon composite material. Preferably, in step S21), the silane mixed gas consists of silane gas and heteroatom gas with a volume ratio ranging from 10:0.5-2 and a flow rate ranging from 100-500 SCCM. The silane gas is any one or a mixture of silane, silane, and chlorosilane; the heteroatom gas is any one or a mixture of boron hydride, hydrogen sulfide, ammonia, and hydrogen boride; and / or the oxygen-containing gas is any one or a mixture of oxygen, carbon monoxide, carbon dioxide, nitric oxide, nitrogen dioxide, sulfur dioxide, and formaldehyde.
[0032] S22) According to the mass ratio of silicon-carbon composite material: silane coupling agent: asphalt: conductive agent solution in the range of 100:0.5-2:1-5:100-500, the silicon-carbon composite material, silane coupling agent, asphalt and conductive agent solution obtained in step S21) are added to the carbonization equipment and dispersed evenly. Then, the mixture is carbonized at a temperature of 250-400°C at a rate of 1-5°C / min for at least 1 hour, preferably 1-6 hours, and then heated to 900-120°C. The material is kept at 0°C for at least 1 hour, preferably 1-6 hours, and then cooled under an inert atmosphere to obtain a secondary particulate silicon-carbon composite material. Preferably, in step S22), the silane coupling agent is γ-mercaptopropyltriethoxysilane (KH-580), γ-aminopropyltriethoxysilane (KH-550), γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560), or bis-(γ-triethoxysilylpropyl)tetrasulfide (S). The mixture is one or more of i 69) and bis(triethoxysilylpropyl) disulfide (Si 75); and / or the asphalt is one or more of coal tar pitch, petroleum asphalt and emulsified asphalt, with a preferred softening point range of 100-140℃, a preferred volatile content of ≤60%, and a preferred coking value of ≥40%; preferably, in step S22), the conductive agent concentration in the conductive agent solution is in the range of 0.5-5wt%, the conductive agent is one or more of carbon nanotubes, graphene, carbon black and fumed carbon fibers, and / or the solvent in the conductive agent solution is N-methylpyrrolidone.
[0033] Preferably, in this embodiment, secondary particulate silicon-carbon composite material is used as the active material raw material for preparing battery electrode sheets, and more preferably as the active material raw material for lithium-ion battery negative electrode sheets.
[0034] Those skilled in the art can apply this method according to actual needs. The specific application method should be a conventional technical means for those skilled in the art. Therefore, this embodiment does not impose any particular limitation on its application method.
[0035] To enable those skilled in the art to better understand the technical solutions of this invention, the technical solutions of the embodiments of this invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of this invention.
[0036] Based on the above-described implementation schemes, this application further proposes the following specific embodiments:
[0037] Example 1: This Example 1 describes the preparation of secondary particulate silicon-carbon composite material according to the following steps:
[0038] Preparation of mesoporous silicon-carbon composite materials:
[0039] S11) Mix 100g of silica molecular sieve (0.5nm-2nm), 5g of ZnCl2 and 20g of sodium citrate evenly and add them to 3000g of N-methylpyrrolidone solution of 10wt% polyimide resin and disperse evenly to obtain a mixture.
[0040] S12) After spray drying the mixture obtained in step S11), it is pre-carbonized at 600°C for 12 hours and washed with 1000g of 0.1mol / L hydrochloric acid to obtain the pre-carbonized intermediate material.
[0041] S13) The pre-carbonized intermediate material obtained in step S12) is transferred to a tube furnace, and carbon dioxide active gas (flow rate of 1000 SCCM) is introduced. The material is carbonized at 950°C for 3 hours to obtain a mesoporous silicon-carbon composite material.
[0042] S21) The mesoporous silicon-carbon composite material obtained above is transferred to a fluidized bed and a silane mixed gas (silane to boron hydride volume ratio = 10:1, flow rate 300 SCCM) is introduced. The silicon-carbon precursor material is obtained by pyrolysis at a temperature of 450℃. Then, the temperature is lowered to 250℃ and oxygen gas with a flow rate of 300 SCCM is introduced for 120 minutes to obtain the silicon-carbon composite material.
[0043] S22) 100g of the silicon-carbon composite material obtained in step S21), 1g of γ-mercaptopropyltriethoxysilane, 3g of coal tar pitch and 300g of 1wt% carbon nanotube conductive agent solution were added to a horizontal rotary furnace and dispersed evenly. Then, the temperature was raised to 300°C at a rate of 3°C / min for carbonization for 3 hours. After that, the temperature was raised to 1000°C and held for 3 hours. Then, the temperature was cooled to room temperature under an argon inert atmosphere to obtain the secondary particle silicon-carbon composite material provided in Example 1.
[0044] This application conducted SEM tests on the secondary particle silicon-carbon composite material provided in Embodiment 1, and the test results are as follows: Figure 3 As shown; by Figure 3 It can be seen that the material exhibits a secondary granular structure, and the particle size distribution is uniform, with particle sizes ranging from 10 to 15 μm.
[0045] Example 2: In this example, secondary particulate silicon-carbon composite material was prepared according to the following steps:
[0046] Preparation of mesoporous silicon-carbon composite materials:
[0047] S11) Mix 100g of silica molecular sieve (0.5nm-2nm), 1g of ZnNO3 and 10g of magnesium citrate evenly and add them to 200g of N-methylpyrrolidone solution of 5wt% urea-formaldehyde resin and disperse evenly to obtain a mixed solution.
[0048] S12) After spray drying the mixture obtained in step S11), it is pre-carbonized at 500°C for 24 hours and washed with 1000g of 0.1mol / L hydrochloric acid to obtain the pre-carbonized intermediate material.
[0049] S13) The pre-carbonized intermediate material obtained in step S12) is transferred to a tube furnace, and carbon dioxide active gas (flow rate of 500 SCCM) is introduced. The material is carbonized at 1200°C for 1 hour to obtain a mesoporous silicon-carbon composite material.
[0050] S21) The mesoporous silicon-carbon composite material obtained above is transferred to a fluidized bed and a silane mixed gas (silane and hydrogen sulfide volume ratio = 10:0.5, flow rate 100 SCCM) is introduced. The silicon-carbon precursor material is obtained by pyrolysis at a temperature of 400℃. Then, the temperature is lowered to 200℃ and carbon dioxide gas with a flow rate of 100 SCCM is introduced for 300 minutes to obtain the silicon-carbon composite material.
[0051] S22) 100g of the silicon-carbon composite material obtained in step S21), 0.5g of γ-aminopropyltriethoxysilane, 1g of petroleum asphalt and 100g of 5wt% graphene conductive agent solution were added to a horizontal rotary furnace and dispersed evenly. Then, the temperature was raised to 250°C at a rate of 1°C / min for carbonization for 6 hours, followed by heating to 900°C and holding for 6 hours. After that, the temperature was cooled to room temperature under an argon inert atmosphere to obtain the secondary particle silicon-carbon composite material provided in Example 2.
[0052] Example 3: In this example, secondary particulate silicon-carbon composite material was prepared according to the following steps:
[0053] Preparation of mesoporous silicon-carbon composite materials:
[0054] S11) Mix 100g of silica molecular sieve (pore size 0.5-2nm), 10g of ZnCO3 and 30g of zinc citrate evenly and add them to 2000g of N-methylpyrrolidone solution of 25wt% benzoxazine resin and disperse evenly to obtain a mixed solution.
[0055] S12) After spray drying the mixture obtained in step S11), it is pre-carbonized at 700°C for 6 hours and washed with 1000g of 0.1mol / L hydrochloric acid to obtain the pre-carbonized intermediate material.
[0056] S13) The pre-carbonized intermediate material obtained in step S12) is transferred to a tube furnace, and carbon dioxide active gas (flow rate of 2000 SCCM) is introduced. The material is carbonized at 800°C for 6 hours to obtain a mesoporous silicon-carbon composite material.
[0057] S21) The mesoporous silicon-carbon composite material obtained above is transferred to a fluidized bed and a chlorosilane mixed gas (the volume ratio of chlorosilane to ammonia is 10:2) is introduced. The silicon-carbon precursor material is obtained by pyrolysis at a temperature of 500℃. Then, the temperature is lowered to 300℃ and nitrogen dioxide gas with a flow rate of 500 SCCM is introduced for 30 minutes to obtain the silicon-carbon composite material.
[0058] S22) 100g of the silicon-carbon composite material obtained in step S21), 2g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 5g of emulsified asphalt, and 500g of 0.5wt% carbon black conductive agent solution were added to a horizontal rotary furnace for uniform dispersion. Then, the temperature was increased to 400°C at a rate of 5°C / min for carbonization for 1 hour, followed by heating to 1200°C and holding for 1 hour. After that, the temperature was cooled to room temperature under an argon inert atmosphere to obtain the secondary particle silicon-carbon composite material provided in Example 3.
[0059] Comparative Example 1: The remaining technical solutions of Comparative Example 1 are the same as those of Example 1, except that in step S21) of Comparative Example 1, the silane mixed gas is replaced with silane gas, and after the silicon-carbon precursor material is obtained by pyrolysis, step S21) is completed and no further oxygen gas is introduced.
[0060] Comparative Example 2: The remaining technical solutions of Comparative Example 2 are the same as those of Example 1, except that step S22) is omitted in Comparative Example 2, and the silicon-carbon composite material obtained by step S21) of Example 1 is directly used.
[0061] Comparative Example 3: The remaining technical solutions of Comparative Example 3 are the same as those of Example 1, except that step S11) of Comparative Example 3 is replaced by: adding 100g of silica molecular sieve to 3000g of N-methylpyrrolidone solution of 10wt% polyimide resin and dispersing it evenly to obtain a mixture.
[0062] Comparative Example 4: The rest of the technical solutions of Comparative Example 4 are the same as those of Example 1, except that the preparation of mesoporous silicon-carbon composite material is omitted in Comparative Example 4, and the silica molecular sieve used in step S11) of Example 1 is directly used to replace the mesoporous silicon-carbon composite material used in step S21).
[0063] Comparative Example 5: The remaining technical solutions of Comparative Example 5 are the same as those of Example 1, except that Comparative Example 5 omits the preparation of mesoporous silicon-carbon composite material and directly uses the sintered phase (i.e., the composite material of nano-silicon and mesoporous carbon) obtained in step (c) of Example 1 of the prior published patent CN109755555A to replace the mesoporous silicon-carbon composite material used in step S21).
[0064] Comparative Example 6: The remaining technical solutions of Comparative Example 6 are the same as those of Example 1, except that the preparation of mesoporous silicon-carbon composite material is omitted in Comparative Example 6, and the mesoporous silicon-carbon composite material used in step S21) is directly adopted from the mesoporous carbon spheres provided in Example 1 of the prior published patent CN113264517A.
[0065] To compare and verify the effects of Examples 1-3 and Comparative Examples 1-6 above, this application conducted the following physicochemical properties and coin cell tests on the silicon-carbon composite materials obtained in Examples 1-3 and Comparative Examples 1-6:
[0066] 1) The specific surface area and tap density of the silicon-carbon composite materials obtained in Examples 1-3 and Comparative Examples 1-6 were tested according to the methods in the national standard GB / T 38823-2020 "Silicon-Carbon". The resistivity of each silicon-carbon composite material was tested using a four-probe tester. The test results are shown in Table 1 below.
[0067] 2) Button cell battery test:
[0068] The silicon-carbon composite materials obtained in Examples 1-3 and Comparative Examples 1-6 were used as the active materials for the negative electrode sheets of the batteries to prepare and assemble nine coin cells. The specific preparation process of each coin cell is as follows:
[0069] Preparation of battery negative electrode sheet: A binder, a conductive agent, and a solvent were added to the silicon-carbon composite materials (as active materials for battery negative electrode sheets) corresponding to Examples 1-3 and Comparative Examples 1-6, respectively. The mixture was stirred and slurried, coated on copper foil, and dried and rolled to obtain the battery negative electrode sheets. The binder was polyvinylidene fluoride (PVDF), the conductive agent was SP (conductive carbon black), and the solvent was N-methylpyrrolidone (NMP). The ratio was: silicon-carbon composite material: SP: PVDF: NMP = 95g: 1g: 4g: 220mL.
[0070] Coin cell preparation: The electrolyte used was a LiPF6 solution with a concentration of 1 mol / L. The solvent used was a 1:1 weight ratio mixture of ethylene carbonate (EC) and diethyl carbonate (DEC). A lithium metal sheet was used as the counter electrode, and a polypropylene (PP) membrane was used as the separator. The simulated battery was assembled in an argon-filled glove box. The electrochemical performance was tested on a Wuhan Landian CT2001A battery tester under the following conditions: charge / discharge voltage range of 0.005V to 2.0V, and charge / discharge rate of 0.1C. The rate performance (1C / 0.1C) of each coin cell was also tested, and the test results are shown in Table 1 below.
[0071] This application also conducted a full-charge expansion test on the above-mentioned button cell. The specific test process is as follows: the thickness D1 of the negative electrode sheet of the rolled button cell is measured. Then, the negative electrode sheet of the button cell is dissected at 100% SOC and its thickness D2 is measured. Then, the full-charge expansion rate is calculated as (D2-D1) / D1*100%. The test results are shown in Table 1 below.
[0072] Table 1
[0073]
[0074] As shown in Table 1 above, the coin cells made using the silicon-carbon composite materials provided in Examples 1-3 of this application are significantly better than those of Comparative Examples 1-6 in terms of initial discharge specific capacity, initial efficiency, and rate capability (1C / 0.1C).
[0075] 3) Pouch battery test:
[0076] The silicon-carbon composite materials obtained in Examples 1-3 and Comparative Examples 1-6 were each doped with 90% artificial graphite as negative electrode materials (i.e., negative electrode sheets), with ternary material LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 was used as the positive electrode material, electrolyte, and separator to assemble a 5Ah pouch battery. The separator was Celegard 2400, and the electrolyte was a LiPF6 solution. The LiPF6 solution was a 1:1 volume ratio mixture of EC and DEC, with a LiPF6 concentration of 1.3 mol / L. The following performance tests were performed on each negative electrode and its corresponding pouch battery:
[0077] A. The following liquid absorption capacity tests were performed on each negative electrode:
[0078] Using a 1 mL burette, 1 mL of electrolyte was drawn and added to the surface of the corresponding negative electrode. Timing was maintained until the electrolyte was completely absorbed, and the time t was recorded. The test results are shown in Table 2 below.
[0079] Table 2
[0080] Example 1 54 Example 2 48 Example 3 61 Comparative Example 1 59 Comparative Example 2 47 Comparative Example 3 73 Comparative Example 4 87 Comparative Example 5 79 Comparative Example 6 76
[0081] As can be seen from Table 2 above, the silicon-carbon composite materials obtained in Examples 1-3 of this embodiment have excellent liquid absorption and retention capabilities.
[0082] B. The following cycle performance tests and rate tests were conducted on each pouch cell:
[0083] The test conditions for the cycle performance test were: charge / discharge voltage range of 2.5 to 4.2V, temperature of 25±3.0℃, charge / discharge rate of 1.0C / 1.0C, and 500 cycles; the test results are shown in Table 3 below.
[0084] The test conditions for the rate test are as follows: each soft pack battery is charged to 4.2V at a constant current of 2C, and then charged to 100% SOC at a constant voltage of 0.1C. The 2C constant current ratio is calculated as 2C constant current capacity / (2C constant current capacity + 0.1C constant voltage capacity). The test results are shown in Table 3 below.
[0085] Table 3
[0086]
[0087] As shown in Table 3 above, the soft-pack lithium-ion batteries prepared using the silicon-carbon composite materials provided in Examples 1-3 of this application exhibit significantly better rate performance and cycle performance than Comparative Examples 1-6.
[0088] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No reference numerals in the claims should be construed as limiting the scope of the claims.
[0089] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. An application of a mesoporous silicon-carbon composite material, characterized in that, The preparation method of the mesoporous silicon-carbon composite material includes the following steps: S11) The silica molecular sieve, activator, and organic carbonate are mixed evenly and added to the resin solution for uniform dispersion to obtain a mixture; the mass ratio of the silica molecular sieve, activator, organic carbonate, and resin is in the range of 100:1-10:10-30:100-500; the activator is any one or a mixture of ZnCl2, ZnNO3, and ZnCO3; and / or the organic carbonate is any one or a mixture of sodium citrate, magnesium citrate, zinc citrate, calcium citrate, diammonium hydrogen citrate, ammonium hydrogen citrate, and ammonium citrate; S12) After spray drying the mixture obtained in step S11), pre-carbonize it at a temperature of 500-700℃ for at least 5 hours, and after acid washing, obtain the pre-carbonized intermediate material. S13) The pre-carbonized intermediate material obtained in step S12) is transferred to a carbonization device, and carbon dioxide active gas with a flow rate range of 500-2000 SCCM is introduced into the carbonization device. The carbonization is carried out for 1-6 hours at a temperature of 800-1200℃ to obtain the mesoporous silicon-carbon composite material. The mesoporous silicon-carbon composite material is used as a raw material for preparing secondary particulate silicon-carbon composite material, wherein the secondary particulate silicon-carbon composite material includes the following preparation steps: S21) The mesoporous silicon-carbon composite material is transferred to a fluidized bed, and a silane mixed gas is introduced. The material is then pyrolyzed at a temperature of 400-500℃ to obtain a silicon-carbon precursor material. The temperature is then lowered to 200-300℃, and an oxygen-containing gas with a flow rate of 100-500 SCCM is introduced for 30-300 minutes to obtain the silicon-carbon composite material. In step S21), the silane mixed gas consists of silane gas and heteroatom gas with a volume ratio ranging from 10:0.5-2 and a flow rate ranging from 100-500 SCCM. The silane gas is any one or a mixture of methanesilane, ethylsilane, and chlorosilane; the heteroatom gas is any one or a mixture of boron hydride, hydrogen sulfide, ammonia, and hydrogen boride. S22) According to the mass ratio of silicon-carbon composite material: silane coupling agent: asphalt: conductive agent solution in the range of 100:0.5-2:1-5:100-500, the silicon-carbon composite material, silane coupling agent, asphalt and conductive agent solution obtained in step S21) are added to the carbonization equipment and dispersed evenly. Then, the temperature is increased to 250-400℃ at 1-5℃ / min and carbonized for at least 1 hour. Then, the temperature is increased to 900-1200℃ and held for at least 1 hour. Then, the temperature is lowered in an inert atmosphere to obtain the secondary particle silicon-carbon composite material.
2. The application of the mesoporous silicon-carbon composite material according to claim 1, characterized in that, In step S11), the resin concentration in the resin solution ranges from 5 to 25 wt%, wherein the resin is any one or a mixture of several of urea-formaldehyde resin, polyimide resin, benzoxazine resin and polyarylacetylene resin; and / or the solvent in the resin solution is N-methylpyrrolidone.
3. The application of the mesoporous silicon-carbon composite material according to claim 1, characterized in that, In step S12), pre-carbonization is carried out at a temperature of 500-700℃ for 6-24 hours.
4. The application of the mesoporous silicon-carbon composite material according to claim 1, characterized in that, In step S21), the oxygen-containing gas is any one or a mixture of several of the following: oxygen, carbon monoxide, carbon dioxide, nitric oxide, nitrogen dioxide, sulfur dioxide, and formaldehyde.
5. The application of the mesoporous silicon-carbon composite material according to claim 1, characterized in that, In step S22), carbonization is carried out for 1-6 hours at a temperature of 250-400°C, with the temperature increased at a rate of 1-5°C / minute.
6. The application of the mesoporous silicon-carbon composite material according to claim 1, characterized in that, In step S22), the temperature is then raised to 900-1200°C and held for 1-6 hours.
7. The application of the mesoporous silicon-carbon composite material according to claim 1, characterized in that, In step S22), the silane coupling agent is any one or a mixture of several of γ-mercaptopropyltriethoxysilane (KH-580), γ-aminopropyltriethoxysilane (KH-550), γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560), bis-(γ-triethoxysilylpropyl)tetrasulfide (Si69), and bis(triethoxysilylpropyl)disulfide (Si75); and / or the asphalt is any one or a mixture of several of coal tar pitch, petroleum asphalt, and emulsified asphalt.
8. The application of the mesoporous silicon-carbon composite material according to claim 7, characterized in that, The softening point of the asphalt is 100-140℃, the volatile matter is ≤60%, and the coking value is ≥40%.
9. The application of the mesoporous silicon-carbon composite material according to claim 1, characterized in that, In step S22), the concentration of the conductive agent in the conductive agent solution is in the range of 0.5-5 wt%, and the conductive agent is any one or a mixture of several of carbon nanotubes, graphene, carbon black and fumed carbon fibers, and / or the solvent in the conductive agent solution is N-methylpyrrolidone.
10. The application of the mesoporous silicon-carbon composite material according to claim 1, characterized in that, The secondary particulate silicon-carbon composite material is used as the active material raw material for preparing battery electrodes.
11. The application of the mesoporous silicon-carbon composite material according to claim 1, characterized in that, The secondary particulate silicon-carbon composite material is used as the active material raw material for the negative electrode sheet of a lithium-ion battery.
Citation Information
Patent Citations
Silicon-carbon material and preparation method thereof
CN109755555A
Mesoporous carbon sphere as well as preparation method and application thereof
CN113264517A
Preparation method of silicon and carbon composite microspheres and application thereof
CN101944596A
Fluidized bed preparation method of silicon-carbon composite material, silicon-carbon composite material and application
CN116588933A